Hydrocarbon Biogeochemical Setting of the Baffin Island Oil Spill Experimental Sites. III. Biota - Cretney, Walter J.; Green, David R.; Fowler, Brian R.; Humphrey, Blair; Engelhardt, F. Rainer; Norstrom, Ross J.; Simon, M.; Fiest, David L.; Boehm, Paul D. (ARCTIC, 1987)
A baseline for petroleum residues in the Cape Hatt region of Baffin Island in arctic Canada was obtained in anticipation of controlled oil releases of the Baffin Island Oil Spill (BIOS) Project. Tissue hydrocarbons in a variety of arctic marine species were dominated by biogenic hydrocarbons. UV/F analysis of tissues indicated an upper limit of petroleum residues in the low to sub micro g/g concentration range. PAHs were detected in samples in the low ng/g concentration range and revealed a distribution of the combustion type. The hydrocarbon baseline in the BIOS study area was found to be as low as might be found anywhere on earth and therefore ideally suited to the BIOS study.Key words: BIOS, arctic marine Canada, hydrocarbon baseline, organisms Mots clés: BIOS, Arctique marin canadien, niveau de référence d’hydrocarbures, organismes